Selective Antegrade Cerebral Perfusion With or Without Additional Lower Body Perfusion During Aortic Arch Reconstruction in Infants. Issue 1 (January 2020) - Kulyabin, Yuriy Y.; Gorbatykh, Yuriy N.; Soynov, Ilya A.; Zubritskiy, Alexey V.; Voitov, Alexey V.; Bogachev-Prokophiev, Alexander V.
Background: Aortic arch reconstruction is often challenging, especially in infants, owing to its high postoperative complication risks. This study aimed to compare the effectiveness between selective antegrade cerebral perfusion (SACP) alone and SACP in combination with continuous lower body perfusion with descending aortic cannulation (DAC) in preserving renal function, and to determine the influence of perfusion strategy on the postoperative course of infants who underwent aortic arch reconstruction. Material and Methods: A total of 121 infants who underwent aortic arch reconstruction between January 2008 and December 2018 were included in the analysis. Patients (median age: 29 days, range: 3-270 days) were divided into the following groups: those who underwent repair with SACP (SACP group, 79 patients) and those who underwent additional lower body perfusion (DAC group, 42 patients). Results: Three (7.1%) and nine (11.4%) patients died in the DAC and SACP groups, respectively ( P = .54). The SACP group had more patients requiring renal replacement therapy ( P = .002) and higher incidence of second stage acute kidney injury (AKI) development (Kidney disease improving global outcomes (KDIGO) criteria; P = .032). The SACP group had higher frequency of open chest postoperatively than the DAC group ( P = .011). The DAC group had lower vasoactive inotropic score (VIS) at the first postoperative day ( P < .001) and shorter intensive care unit length of stay ( P = .050). There was no difference in neurological complications between the groups ( P = .061). High VIS was associated with early mortality (odds ratio [OR]: 1.79 [1.33-2.41], P < .001) and AKI (OR: 1.60 [1.35-1.91], P < .001). The DAC perfusion strategy with minimal hypothermia was associated with lower risk of AKI (OR: 0.91 [0.84-0.98], P = .016). Conclusion: Antegrade cerebral perfusion with continuous lower body perfusion via DAC could effectively be used for improving early postoperative results among infants undergoing procedures that include aortic arch reconstruction.